Budidaya Biokonversi Larva Black Soldier Fly (BSF) dan Puyuh Petelur dalam Pengolahan Sampah Organik untuk Pelestarian Lingkungan pada Tempat Pemrosesan Akhir (TPA) Desa Pacul Kabupaten Bojonegoro - Aziz, Suudin; Ari Abi Aufa; Hendra Setiawan; Irvia Nazilatul Q (LP3M IAIFA Kediri, 2023)
The use of BSF fly larvae using the Bioconversion method in landfills Pacul as organic waste decomposing organisms is a breakthrough for processing organic waste. The advantage of using BSF technology is that it can help reduce the amount of organic waste by up to 80%.. After the maggot is large because it decomposes waste, it can be used as the main feed in raising laying quails. Maggot can be highly nutritious animal feed because it contains substances needed by the growth and development of livestock, especially quail. But the effect was not significant on daily egg production, feed consumption, meat weight and feed conversion of laying quails. Maggot also has the ability to use quail droppings as food which makes him grow big and can be used as a good feed ingredient in living conditions. Maggot is the right solution for livestock, considering the high price of manufactured feed.